Combined effects of ultraviolet radiation and xenobiotics on zebrafish - Almeida, Ana Rita Marques (2014)
Nowadays, climate changes are an imperative problem and multiple measurements made in the last years showed an increase of all wavelengths of solar radiance, specially the Ultraviolet radiation. In their natural environment organisms are not only affected by biotic and environmental factors, but also by abiotic factors such as xenobiotics. Besides, these both stressors can interact with each other being their combined effect unpredictable (producing additive, synergistic or antagonistic effect). This work aims to studying the combined effect of UV radiation and three xenobiotics: triclosan, potassium dichromate and prochloraz on zebrafish embryos (Danio rerio). Effects were assessed at two levels: i) effects on embryos mortality and ii) effects in the natural bacterial communities of zebrafish embryos. The organisms were exposed to concentrations of each chemical combined with several UV doses. Embryo’ mortality, were observed daily for 96 hours post fertilization (hpf) and natural bacterial communities’ evaluation was performed at 48 hpf. Results showed that different combined effect may occur compromising organism’s survival. Combined exposure of UV radiation with TCS revealed a synergism pattern when the UV radiation is the dominant stressor while PD and PCZ revealed antagonism at low dose levels or when the UV radiation is dominant in the mixture. Zebrafish natural bacterial communities were also affected by UV radiation and chemicals with the change of their structure; however, conclusions about interactive effects were difficult to be drawn because effects were not always translated into changes in the diversity indexes.